In-Service Training and Its Effect on the Implementation of Play-Based Learning in ECE Classrooms - Dr. Kiran Akhtar; Dr. Ali Gul Bugti; Dr. Um E Rubab; Erum Noreen; Dr. Sidra Kiran (Research Journal of Psychology, 2025)
Learning occurs swiftly, particularly in the first few years of life. ECE programs formalize the development of core concepts, abilities, and attitudes that lay the groundwork for school readiness. Training is the most efficient approach for giving in-service trainers with knowledge and thinking and preparing them for their performance profession. Early Childhood Education level is beneficial to children's balanced Social, Mental, Physical, and Cognitive development. Given the importance and effectiveness of ECE, all governments prioritize ECE level programs. In-service training is essential for in-service teachers to deal with new challenges and advancements in the educational field. The purpose of this study is to look into the impact of in-service teacher training on teacher performance at the ECE level, as well as the implementation of in-service teacher training programs in Tehsil Chakwal. The study concentrated on in-service instructors and ECE students. The key goals of the study were to look into the impact of teacher performance and the implementation program in Tehsil Chakwal. The study's population includes all early childhood educators from Tehsil Chakwal's government schools, that is 322. To gather samples from ECEs in Tehsil Chakwal, basic random sampling was used, utilizing a questionnaire as a tool instrument. The equipment was self-designed to meet the research requirements. As a sample, 175 ECEs from government schools were selected. The data was analysed using the Statistical Package for Social Sciences (SPSS). The Social Sciences founded a descriptive technique. To calculate percentages and regressions, SPSS was used. The study revealed that trained teachers have better rapport with children as compared to untrained teachers. Trained teachers are more satisfied than untrained teachers. ECE training has improved teachers’ performances and the enrollment of children. Moreover, It contributes to the reduction of dropouts and repeaters at the ECE level.